2018
DOI: 10.7554/elife.38358
|View full text |Cite
|
Sign up to set email alerts
|

Human T cell receptor occurrence patterns encode immune history, genetic background, and receptor specificity

Abstract: The T cell receptor (TCR) repertoire encodes immune exposure history through the dynamic formation of immunological memory. Statistical analysis of repertoire sequencing data has the potential to decode disease associations from large cohorts with measured phenotypes. However, the repertoire perturbation induced by a given immunological challenge is conditioned on genetic background via major histocompatibility complex (MHC) polymorphism. We explore associations between MHC alleles, immune exposures, and share… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
105
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 53 publications
4
105
0
Order By: Relevance
“… by Dewitt et al . identified clusters of TCRs that co‐occur with certain MHC‐alleles, many of which contained previously identified TCRs specific to common pathogens. Second, for some epitopes there might be few or no public sequences .…”
Section: Clonal Sharingmentioning
confidence: 93%
See 1 more Smart Citation
“… by Dewitt et al . identified clusters of TCRs that co‐occur with certain MHC‐alleles, many of which contained previously identified TCRs specific to common pathogens. Second, for some epitopes there might be few or no public sequences .…”
Section: Clonal Sharingmentioning
confidence: 93%
“…First, for TCRs, sharing depends on the recognition of the same epitope, where the implication is that the antigen is presented by the same or highly similar MHC-alleles. A reanalysis of the abovementioned data from Emerson et al [88] by Dewitt et al [97] identified clusters of TCRs that co-occur with certain MHC-alleles, many of which contained previously identified TCRs specific to common pathogens. Second, for some epitopes there might be few or no public sequences [98].…”
Section: Clonal Sharingmentioning
confidence: 97%
“…Consistent with the frequent exposure to common viral pathogens, such as human cytomegalovirus, human papillomavirus and hepatitis C virus, in humans, epitopes from these viruses were found to cross‐react with neoantigens in cancer patients (Table ). Interestingly, the frequencies of TCR repertoire recognising these common pathogens are higher because of the clonal expansion . Thus, it is most likely that the neoantigens that cross‐react with antigens of common pathogens elicit more robust T‐cell response as a result of recalling heterologous memory response than those neoantigens that are recognised by naïve T cells.…”
Section: Pre‐existing Heterologous Immunity Affects Subsequent T‐cellmentioning
confidence: 99%
“…Interestingly, the frequencies of TCR repertoire recognising these common pathogens are higher because of the clonal expansion. 61 Thus, it is most likely that the neoantigens that cross-react with antigens of common pathogens elicit more robust T-cell response as a result of recalling heterologous memory response than those neoantigens that are recognised by na€ ıve T cells.…”
Section: Pre-existing Heterologous Immunity Affects Subsequent T-cellmentioning
confidence: 99%
“…Existing computational methods for TCR repertoire annotation allow both matching against a database of known antigen specificities [12], [13] and clustering of TCR sequences for de novo motif detection [4], [14]. Annotation of a large number of TCR repertoires from healthy donors [15], [16] demonstrates both high variance of frequencies of epitope-specific T-cells and the imprint of past and ongoing pathogen encounters. Thus, de novo discovery of Tcells associated with antigens of interest or certain disease appears to be a hard problem, complicated by the biases in the structure of the naive (unperturbed) TCR repertoire [17], presence of existing clonal expansions specific to unrelated pathogens and high number of false positives that result from the extremely high diversity of the TCR repertoire.…”
mentioning
confidence: 99%